2010
DOI: 10.1073/pnas.0909299107
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of angiogenesis and tumor growth with an orally active drug that stabilizes the inactive state of PDGFRβ/B-RAF

Abstract: Kinases are known to regulate fundamental processes in cancer including tumor proliferation, metastasis, neovascularization, and chemoresistance. Accordingly, kinase inhibitors have been a major focus of drug development, and several kinase inhibitors are now approved for various cancer indications. Typically, kinase inhibitors are selected via high-throughput screening using catalytic kinase domains at low ATP concentration, and this process often yields ATP mimetics that lack specificity and/or function poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 43 publications
0
50
0
Order By: Relevance
“…Inhibition of PDGFb signaling can indirectly reduce tumor vascularization but does not necessarily retard tumor growth (38). Several studies have shown that the dual targeting of endothelial cells and pericytes is more efficient than targeting either cell type alone, even in established or drug-resistant tumors (39)(40)(41). Therefore, blocking Olfml3 holds promise for more effective strategies to control tumor growth by targeting a single molecule that affects 2 distinct cell types within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of PDGFb signaling can indirectly reduce tumor vascularization but does not necessarily retard tumor growth (38). Several studies have shown that the dual targeting of endothelial cells and pericytes is more efficient than targeting either cell type alone, even in established or drug-resistant tumors (39)(40)(41). Therefore, blocking Olfml3 holds promise for more effective strategies to control tumor growth by targeting a single molecule that affects 2 distinct cell types within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…KG5 is a kinase inhibitor of RAF, PDGFR α and β, FLT3 and KIT (29), whereas KG1 targets PDGFR α and β, FLT3 and KIT but not RAF (29). Vatalanib targets KIT, PDGFR and VEGFR (40).…”
Section: Discussionmentioning
confidence: 99%
“…To identify which other targets of sorafenib are critical for CLL cell viability, and therefore might contribute to sorafenib-mediated cytotoxicity, we compared a set of inhibitors sharing overlapping targets with sorafenib for their ability to abrogate CLL cell viability ( Figure 7A). We tested KG5, a kinase inhibitor of RAF signaling through B-RAF and C-RAF in addition to PDGFR α and β, FLT3 and KIT (29), and KG1, a kinase inhibitor that targets all of these kinases except B-and C-RAF (29) and compared their activity on CLL cell viability. In CLL cells cultured alone (Figure 7B) or in the presence of MSCs (Figures 7C, D), KG5 but not KG1 induced CLL cell apoptosis.…”
Section: Cll Cells Are Not Sensitive To Inhibition Of Kit Pdgfr and mentioning
confidence: 99%
“…[41][42][43][44] Karen et al 41 investigated the effects of PC-targeting small molecules, more specifically, whether valproic acid, a histone deacetylase inhibitor, influenced PC proliferation. Other small molecules including trichostatic A and 2-Et-4-Me-Penta were also tested in comparison with valproic acid.…”
mentioning
confidence: 99%
“…The efforts to synthesize novel small molecule drugs have increased since imatinib and sorafenib showed the potential to target PDGFR-β and B-RAF, stabilizing inactive kinase conformations, thus disrupting only PC activity. 42,44 As an example of PC-targeting synthetic small molecules, amino triazole scaffolds act at an allosteric conformational site on kinase due to hydrophobic and specific hydrogen bonding. Using an allosteric approach, synthesized novel small molecules with an amino triazole functional group selectively disrupted angiogenesis and tumor growth by stabilizing the inactive site of PRGFR-β and B-RAF in orthotropic pancreatic and renal carcinoma models.…”
mentioning
confidence: 99%